2017
DOI: 10.3791/55094-v
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Hydrogels from Pulmonary Extracellular Matrix for 3D Cell Culture

Abstract: Here we present a method for establishing multiple component cell culture hydrogels for in vitro lung cell culture. Beginning with healthy en bloc lung tissue from porcine, rat, or mouse, the tissue is perfused and submerged in subsequent chemical detergents to remove the cellular debris. Histological comparison of the tissue before and after processing confirms removal of over 95% of double stranded DNA and alpha galactosidase staining suggests the majority of cellular debris is removed. After decellularizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…In addition, viscosity and Young's modulus of porcine-sourced lung hydrogels were reported using parallel Measuring the mechanical properties is not only useful for diseased environment characterization, but also for verification of the success of methodologies designed to alter such properties. While it is clear that the use of different concentrations of the starting ECM material (powder) (Pouliot et al, 2016) and adjusting the pepsin digestion duration (the essential step in generation of a pre-gel ECM-derived substrate) (Pouliot et al, 2020) influences the mechanical properties, one of the initial attempts to specifically modulate the mechanical properties of lung ECM-derived hydrogels was treating the porcine lung ECM with genipin to increase the stiffness (Link et al, 2017). This approach has been extended with thiol-functionalization (Petrou et al, 2020;Saleh et al, 2022), alginate-reinforcing (De Santis et al, 2021) or fibre crosslinking (Nizamoglu et al, 2022a) to allow greater control over mechanical parameters in the lung ECM-derived hydrogels.…”
Section: Lung Ecm-derived Hydrogels For Mimicking Tissue Biomechanica...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, viscosity and Young's modulus of porcine-sourced lung hydrogels were reported using parallel Measuring the mechanical properties is not only useful for diseased environment characterization, but also for verification of the success of methodologies designed to alter such properties. While it is clear that the use of different concentrations of the starting ECM material (powder) (Pouliot et al, 2016) and adjusting the pepsin digestion duration (the essential step in generation of a pre-gel ECM-derived substrate) (Pouliot et al, 2020) influences the mechanical properties, one of the initial attempts to specifically modulate the mechanical properties of lung ECM-derived hydrogels was treating the porcine lung ECM with genipin to increase the stiffness (Link et al, 2017). This approach has been extended with thiol-functionalization (Petrou et al, 2020;Saleh et al, 2022), alginate-reinforcing (De Santis et al, 2021) or fibre crosslinking (Nizamoglu et al, 2022a) to allow greater control over mechanical parameters in the lung ECM-derived hydrogels.…”
Section: Lung Ecm-derived Hydrogels For Mimicking Tissue Biomechanica...mentioning
confidence: 99%
“…Initial studies using porcine lung ECM-derived hydrogels reported successful growth of human and rat mesenchymal stromal (stem) cells (MSCs) in 2016 (Pouliot et al, 2016). Link et al (2017) then described successful culture of mouse MSCs, human alveolar epithelial cells (the cell line A549), human primary microvascular endothelial cells (HpuVECs), and human umbilical vein endothelial cells (HUVECs) in porcine lung ECM-derived hydrogels. The field is now rapidly expanding with additional cells types including murine fibroblasts (Petrou et al, 2020), rat lung MSCs (Falcones et al, 2021) and rat primary alveolar epithelial cells (Marhuenda et al, 2022b) being grown in porcine lung ECM-derived hydrogels.…”
Section: Lung Ecm-derived Hydrogels For Mimicking Cell:matrix Interac...mentioning
confidence: 99%
“…We decellularized lung tissue based on the same procedure described in (Link et al, 2017). We obtained healthy and Su/ CHx left lung lobes from rats from a prior study (Bhagwani et al, 2019).…”
Section: Decellularizing Lung Tissuementioning
confidence: 99%
“…Hence, cell-to-cell interaction as well as with its surrounding is vital for cell mechanical properties development. Cell behavior assessment surrounded by its natural ECM is desirable; otherwise artificial hydrogels mimicking ECM composition and mechanics offer a good compromise 23,[26][27][28] . 3D hydrogels provide physical constraints forcing the cells to adapt morphologically as well as chemically and biologically to an environment similar to that in tissue.…”
Section: Introductionmentioning
confidence: 99%